MANAJEMEN LAYANAN KHUSUS KEGIATAN EKSTRAKURIKULER TEATER UNTUK MENUMBUHKAN JIWA PERCAYA DIRI (STUDI KASUS DI SMA NEGERI 7 MALANG) - Hanna Ayu Rahmawati; Ali Imron; Nurul Ulfatin; Hanna Ayu Rahmawati; Ali Imron (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: The purpose of this study is to describe in detail the management of special servicesfor theater extracurricular activities to foster a soul of confidence in SMA Negeri 7Malang, starting with the description of the theater extracurricular, thecharacteristics of confidence, the school's efforts to foster students 'selfconfidence,'theater extracurricular planning , theater extracurricularimplementation, and theater extracurricular evaluation, supporting and inhibitingfactors in the theater extracurricular activities at SMA Negeri 7 Malang. Thisresearch uses a qualitative approach to the type of case study. The results of thisstudy describe the description of the theater extracurricular activities, thecharacteristics of confidence, the school's efforts to foster a soul of confidencethrough extracurricular activities, the theater extracurricular planning, theimplementation of the theater extracurricular, and the evaluation of the theaterextracurricular, Supporting factors and obstacles in the management of specialservices extracurricular theater activities to foster a soul of confidence in SMANegeri 7 Malang